FOOD SECURITY AND THE OBESITY EPIDEMIC: A THREAT TO MODERN MEDICINE AND GLOBAL HEALTH (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the correlation between food security challenges and the growing obesity epidemic. Globally, poor nutrition, economic inequality, and inappropriate food industry policies are contributing to the rise of obesity, which in turn increases the risk of cardiovascular diseases, diabetes, and other chronic conditions. The article examines epidemiological data, public health consequences, and potential solutions.